Comparison of heart rate variability psychological responses and performance in virtual and real archery - Dal, N.; Tok, S.; Balikçi, I.; Yilmaz, S. E.; Binboga, E. (Brain and Behavior, 2024)
Background: This study examines the psychophysiological differences between virtual reality (VR) and real archery. It explores whether VR archery induces heart rate (HR), heart rate variability (HRV), and breathing rates similar to those experienced in real archery. Additionally, the study assesses differences in perceived anxiety, difficulty, confidence, rate of perceived exertion (RPE), and shooting performance between the two modalities, providing insights into the efficacy of VR as a training tool for archery.